Menghidupkan kembali jiwa yang sudah mati melalui augmented reality (AR): SEMIOTIKA DALAM FILM KETIKA BERHENTI DI SINI - Febriani, Silvy Regina; Taufik, Cevi Mochamad (KOMUNIKA BANGSA, 2025)
This study explores the use of Augmented Reality (AR) technology in the film Ketika Berhenti di Sini, which portrays the protagonist’s attempt to cope with grief over the loss of a loved one through virtual interaction with hologram. The aim of this research is to analyze the denotative, connotative, and mythical meanings of the idea of “reviving a departed soul” through AR technology. This study adopts a qualitative approach using Roland Barthes’ semiotic analysis. Data collection was carried out through visual observation of relevant scenes in the film, which were then analyzed using Barthes’ structure of signs (signifier, signified, denotation, connotation, and myth). The results indicate that the use of AR in the film creates visual and narrative signs that represent the meaning of loss and the attempt  transcend reality. At the denotative level, it depicts real-time interaction with the deceased through a hologram. The connotative meaning reveals the depth of emotional trauma and grief, while the mythical meaning reflects modern cultural hopes for life after death through technological means. The analysis also identifies Barthes' codes (hermeneutic, proairetic, symbolic, and narrative) that contribute to the film’s implicit meanings.